WHAT IS DISTANCE EDUCATION? AN OVERVIEW FROM CONCEPTUAL PERSPECTIVE - Tatlılıoğlu, Kasım (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
Distance education is a multidimensional process involving education conducted over long distances and mediated by instructional technology. Distance education has been made possible in recent times because of the convergence of the growing interest in life long learning and unprecedented rapid developments in information and communication technology. These developments have had great impact on teaching and learning in general and distance education in particular. Distance learning, one of the virtual environments, has eliminated the time and place dependence for the individuals and appealed learning style of each individual. However, the role of technology in education is mostly controlled or directed by the teacher. Distance education is nowadays almost entirely has evolved into an educational activity carried out over the internet. In this study is explained distance education from conceptually perspective.